Speaking of the Intellect, Instinctively - Bonner, Richard F.; Mamchych, Tetyana I. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
To the extent a cognitive artifact extends natural language, questions of the former should be preceded by answers to those of the latter; and, questions about cognitive science and pertinent technology should begin by asking how one may verbalise one’s ideas about cognition, one’s own cognition to start with. One does that, it is plain, in two ways: one talks of one’s thoughts and one’s feelings. One thus sees oneself not as one but as at least two. Not to cause unrest, however, one continues to talk of oneself as one, calling one’s pluralistic faculties in the singular as the Soul or the Intellect, the nest of the classical trivium of the beautiful, the good, and the intelligent. Degraded to tangible by social demand, the Intellect becomes intelligence plain, semantically rooted in behavior, hence operational, prerogative of machine. One’s remaining spiritual faculties, collectively labeled psyche, are something to aid by therapy or drugs to keep one from acting strange. Bottled in rational formaldehyde for almost a century, only recently get they restituted by science as key actors of cognition. But in public space they remain non gratae, increasingly so indeed as the digital strait jacket steadily tightens around people’s souls, taking the spark out of their social and professional presence, the spark that survived both Descartes and Marx. A century after Freud, four after Shakespeare, and four and twenty after Plato, feelings remain a mystery eluding words. Perhaps they should? We share our feelings on these vital mushy matters, irrespectively.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 26-37